Analysing Bharatiya Sanskriti and Dharma-Rajya through the Lens of Deen Dayal Upadhayay - Kashish Jain, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In an attempt to analyse alternatives to the dominant philosophies and provide a direction for India’s developmental path, Deendayal Upadhayay articulated the concept of Integral Humanism rooted deeply in the Bharatiya culture and Dharma leading to holistic development which encompasses social, economic and spiritual dimensions in an integrative manner. This research paper delves deeper into the idea of Integral Humanism which provides solutions through civilizational ethos and values in a cooperative rather than competitive approach to distinctions over bodily traits and objectives of mankind leading to overall development of both personality and the society through decentralised and self-reliant economy in Dharma-Rajya.This secondary research paper is based on the study of existing literature on integral humanism expoundedinUpadhyay’s lectures,the main motive is to understand the basicframework of our tradition and civilisation that has been built over time, advocating for the incorporation of indigenous knowledge patterns into decision making processes. The concepts emphasised below are based on the lectures delivered by Deendayal Upadhyay in the form of four lectures delivered in Bombay in April, 1965.
Keywords: Dharma; Integrative; Balance; Economy; Culture